1997
DOI: 10.1136/sti.73.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Are reported stress and coping style associated with frequent recurrence of genital herpes?

Abstract: Objectives: This paper reports on the cross sectional data from the longitudinal study examining the impact of genital herpes simplex virus (HSV) infection on quality of life. In particular the report sought to study the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 24 publications
(4 reference statements)
0
42
0
2
Order By: Relevance
“…Periodically, reactivation from latency occurs, which is crucial for virus transmission. In general, increased "stress" correlates with a higher incidence of reactivation from latency in humans (Cassidy et al, 1997;Glaser et al, 1985;Padgett et al, 1998). In keeping with these observations, the synthetic corticosteroid dexamethasone accelerates reactivation from latency in TG neuronal cultures or TG organ cultures prepared from mice latently infected with HSV-1 (Du et al, 2012;Halford et al, 1996).…”
Section: Introductionmentioning
confidence: 58%
“…Periodically, reactivation from latency occurs, which is crucial for virus transmission. In general, increased "stress" correlates with a higher incidence of reactivation from latency in humans (Cassidy et al, 1997;Glaser et al, 1985;Padgett et al, 1998). In keeping with these observations, the synthetic corticosteroid dexamethasone accelerates reactivation from latency in TG neuronal cultures or TG organ cultures prepared from mice latently infected with HSV-1 (Du et al, 2012;Halford et al, 1996).…”
Section: Introductionmentioning
confidence: 58%
“…Findings on the contribution of stress are "contradictory and inconclusive". Cassidy et al (1997) did not find any relation between recurrence of genital herpes and anxiety, depression, health locus of control, personality, or social support, but found that active problem-and emotion-focused coping strategies are more likely to be of value in coping with herpetic recurrence. Stronks et al (1993) found that during active symptoms HSV ‡ patients show more anxiety, lower self esteem, have more psychological complaints, more sexual inhibition and greater bitterness toward their partners.…”
Section: Psychological Reactions To Hsv ‡ Diagnosismentioning
confidence: 76%
“…Herpes simplex esteem, and resultant flight in the face of an imminent sexual relationship (Cassidy et al 1997).…”
Section: Hsv-1 Recurrences May Be Elicited By Emotional Stress !mentioning
confidence: 99%